2023
DOI: 10.3390/app13042066
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Sedimentary Rock Porosity Using a Digital Image Analysis

Abstract: Pore space characterisation is important in assessing the strength and hydraulic characteristics of rock. This paper proposes a new relationship to estimate the porosity of natural rocks using the data from a scanning electron microscope (SEM) and a pore and crack analysis system (PCAS). The obtained results were compared with the data obtained from a series of conventional mercury intrusion porosimetry (MIP) experiments. Three different rocks, namely siltstone, sandstone, and coal, collected from a depth belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Density, neutron, and other logs commonly can be used to calculate porosity, whereas shale and its organic component affect the density . Estimating total porosity in shale gas reservoirs poses a challenge due to high clay minerals and fine-grained texture . Log porosity was used to generate a distribution map and to understand the regional porosity behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Density, neutron, and other logs commonly can be used to calculate porosity, whereas shale and its organic component affect the density . Estimating total porosity in shale gas reservoirs poses a challenge due to high clay minerals and fine-grained texture . Log porosity was used to generate a distribution map and to understand the regional porosity behavior.…”
Section: Resultsmentioning
confidence: 99%
“… 48 Estimating total porosity in shale gas reservoirs poses a challenge due to high clay minerals and fine-grained texture. 49 Log porosity was used to generate a distribution map and to understand the regional porosity behavior. It can help understand the prospective of the Patala Formation compared to the surrounding fields having available logs.…”
Section: Resultsmentioning
confidence: 99%
“…They used the ImageJ complement called DiamterJ and analyzed SEM images of fibrin meshes, reporting the diameter measurements and porosity and comparing them with manual measurements and concluded that the algorithms resulted suitable for establishing the diameter through image analysis; the measurements were adjusted to the clot biophysical characteristics and manually determined values. Tan et al [ 18 ] estimated the porosity of natural rocks by means of SEM data and a pore and crack analysis system. These authors concluded that the digital analysis was capable of identifying accurately the pore size and porosity values, which agreed with experimental data.…”
Section: Introductionmentioning
confidence: 99%